Structural Insights into Multi‐Metal Spinel Oxide Nanoparticles for Boosting Oxygen Reduction Electrocatalysis (Adv. Mater. 8/2022). Issue 8 (24th February 2022) - Kim, Jiheon; Ko, Wonjae; Yoo, Ji Mun; Paidi, Vinod K.; Jang, Ho Yeon; Shepit, Michael; Lee, Jongmin; Chang, Hogeun; Lee, Hyeon Seok; Jo, Jinwoung; Kim, Byung Hyo; Cho, Sung‐Pyo; et al.
Abstract : Multi‐Metal Oxide (Electro)catalysts Multi‐metal oxide (MMO) nanomaterials have significant potential to facilitate various demanding (electro)catalytic reactions, but their intrinsic complexity hinders in‐depth understanding of the origin of the catalytic activity. In article number 2107868, Kug‐Seung Lee, Seoin Back, Yung‐Eun Sung, Taeghwan Hyeon, and co‐workers develop a structural understanding of uniform‐sized spinel‐type MMO nanoparticles, which boosts the electrocatalytic oxygen reduction reaction (ORR) activity. Physicochemical and electrochemical analysis reveal the contribution of each element to the structural flexibility and corresponding improved ORR activity.